Perancangan Interior Perpustakaan Fasilitas Multimedia di Surabaya - Setiawan, Yosef (Intra, 2017)
Library is a place that is used to learning and exploring new things in order to broaden the knowledge of the users, nowadays technology is growing more rapidly every year. With the development of technology, it will create a library that not only has collection of books, but it is also has collection of digital file. Furthermore, with rapid growth of young generation that has faster adaptability with technology which is shifting the function of library to tend use more digital file, including video and online documents.This design intended to create a Multimedia Library that users can use at the fullest in accordance with the needs of users by using multimedia facilities that might use cassette and books in library.